Books Completed or in Progress by Academy Members (Academy of Management Journal, 1965)
The article presents a list of books about management. They include “General Administration,” by Preston P. LeBreton, “Business Data Processing,” by Elias M. Awad, and “The Analysis of Organizations,” by Joseph A. Litter.